Children's independent mobility during dark hours: a scoping review - Litsmark, Anna; Rahm, Johan; Mattsson, Pimkamol; Johansson, Maria (Frontiers in Public Health, 2023)
Introduction Independent mobility is every child's right and has implications for their health, wellbeing, and development. This scoping review addresses children's needs and experiences of light conditions in their everyday outdoor life. The review examines peer-reviewed scientific literature that analyses associations between different light conditions and children's independent mobility (CIM) during dark hours. Methods By formulating a Boolean search string, including terms related to children independent mobility, light and outdoor environment, five scientific databases were searched. The search resulted in 67 eligible papers that were analyzed through an inductive, thematic analysis. Results Four overarching themes representing the researched topics of the effects of light conditions with importance for CIM during dark hours were identified: (1) physical activity (PA) and active travel, (2) outdoor activities and place use, (3) safety perception, and (4) outdoor risks. The findings highlight that darkness constitutes a major obstacle for CIM, and that fear of darkness is common among children. It restricts the degree of CIM and influences children's safety perception as well as how they navigate through public places outdoors. The findings show that the type and design of outdoor settings during dark hours and children's familiarity with places during daytime could play a role in the degree of CIM after dark. The presence of outdoor lighting is related to children's increased PA and active travel, and outdoor lighting seems to also influence children's place use and interaction with the environment. The presence and extent of outdoor lighting and lighting quality may play a role in children's safety perception, which in turn can influence CIM. Discussion The findings suggest that promoting CIM during dark hours might not only contribute to the accumulation of children's PA, confidence, and skills, but also support mental health. The understanding of children's perspectives on the quality of outdoor lighting needs to be deepened to support CIM. Highlighting the child perspective would aid the development of current recommendations for outdoor lighting and the implementation of the Agenda 2030 of ensuring healthy lives and promoting wellbeing for all at all ages, and making cities inclusive, safe, resilient and sustainable throughout the day and seasons.